Response inhibition in borderline personality disorder: performance in a go/nogo task - Rentrop, Mirjam; Backenstraß, Matthias; Jäntsch, Britta; Kaiser, Stefan; Roth, Alexander; Unger, Jörg; Weisbrod, Matthias; Renneberg, Babette (Psychopathology, 2008)
Background: Borderline personality disorder is associated with subtle neuropsychological deficits. A potential impairment of response inhibition is of major interest, since it could be related to impulsivity as a clinical feature of borderline personality disorder. Sampling and Methods: Response inhibition was studied in an auditory Go/Nogo paradigm in a sample of 20 female inpatients with borderline personality disorder and 18 healthy controls. The main measures of interest were general task performance, errors and reaction times. Results: Patients with borderline personality disorder performed worse in the Nogo task but not in the Go task. In the Nogo task, when response inhibition was essential, patients made more errors of commission, revealing problems to inhibit a prepotent response. Additionally, the borderline group was characterized by significantly shorter reaction times in both tasks compared to the nonclinical control group. The results for errors of commission in the Nogo task remained significant even after controlling for reaction time. Conclusions: The present results suggest a double impairment on this response inhibition task. First, borderline personality disorder patients have inadequately fast reaction times and a speed-accuracy tradeoff. Second, they show a genuine deficit of response inhibition. These results are discussed in the context of the conflicting literature on response inhibition and executive control in borderline personality disorder.
Published online: November 1, 2007
Gesehen am 14.12.2021